PERANAN ORGANISASI DALAM MENINGKATKAN MOTIVASI TERHADAP KINERJA KARYAWAN - DIAN GUSTRAZAIMAN PURBA TAMBAK (LP2MTBM MAKARIOZ, 2021)
The writing of this paper aims to find out the influence of organizational role and motivation on employee performance. Thewriting of this paper uses the literature review method (research library). From the discussion, it can be concluded thatculture is the implementation of attitudes or combinations of values instilled by the company in order to achieve thecompany's goals. Organizational culture and employees become important criteria in determining the growth and success ofa company. The existence of a good organizational culture can improve employee performance. In addition to organizationalculture, performance is also influenced by employee motivation. Employees who are highly motivated in work will providegood work achievements, while for employees who have low motivation will not give achievements as good as employeeswho have high motivation. All of that is reflected through the attitude of employees in the face of their work, among otherscharacterized by a decrease in work spirit, quickly boredom, frequent absence, late arrival and so on that ultimately all havean impact on the decrease in employee performance.